Wipe-Clean Writing (London Penguin Books Ltd, 2014)
This book helps you practise your handwriting skills with Peppa. You can trace the letters and learn new words in this wipe-clean activity book. It is perfect for young readers who are starting school and developing their writing skills and pencil control. Children can wipe the page clean and practise again and again. Includes a free pen. Look out for Practise with Peppa: Wipe-Clean Numbers too!
Lingu(NE(Bsticss
2
Keywords: Lingu(NE(Bsticss